Nilai-Nilai Pilar Pancasila Sebagai Komitmen Kebangsaan - Anggoro, Sasmitro; Albina, Meyniar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Pancasila, as the foundation of the state and the way of life of the Indonesian nation, plays a central role in maintaining unity and cohesion amidst diversity. The values contained within the five pillars of Pancasila Belief in the One and Only God, Humanity, Unity, Democracy, and Justice serve as a strong foundation for building national commitment. The first pillar, Belief in the One and Only God, emphasizes the importance of spirituality and tolerance among religious communities. The second pillar, Just and Civilized Humanity, highlights respect for human rights and individual dignity. The third pillar, the Unity of Indonesia, promotes an inclusive nationalism amidst cultural, ethnic, and religious diversity. The fourth pillar, Democracy Guided by the Inner Wisdom of Deliberations among Representatives, strengthens democratic values rooted in deliberation and consensus. The fifth pillar, Social Justice for All Indonesian People, underscores the importance of equity and justice in various aspects of community life. The implementation of these values not only serves as an ethical foundation for individuals but also as a guideline for public policymaking. Commitment to Pancasila as the nation's ideology acts as a bulwark against the threats of national disintegration and the challenges of globalization. Therefore, strengthening the understanding and application of Pancasila's values becomes a collective responsibility of all elements of society to safeguard the unity of the Unitary State of the Republic of Indonesia (NKRI). This study recommends integrating Pancasila values education across various sectors, both formal and informal, to reinforce national commitment amidst the challenges of the times.